2023
DOI: 10.3390/rs15153754
|View full text |Cite
|
Sign up to set email alerts
|

Landfill Site Selection Using Multi-Criteria Decision Analysis, Remote Sensing Data, and Geographic Information System Tools in Najran City, Saudi Arabia

Abstract: Many practical issues arise when dealing with solid waste management, and there are also environmental effects to be considered. Selecting landfill sites requires extra care with respect to many factors such as the environment, health hazards for people, and the cost of transportation. Furthermore, cities have their own rules, methods, and practices for managing and selecting the best locations for collecting solid waste. In this research, multi-criteria decision analysis (MCDA) was presented and used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In our study, we opted to use the multidimensional analysis method, which considers a range of criteria influencing the resilience of rural settlements. Most recent research commonly employs the Analytic Hierarchy Process (AHP) methodology for conducting multicriteria assessments across multiple research areas [46][47][48]. The AHP method provides a systematic framework for decision-making by establishing a hierarchical structure that captures the various dimensions, criteria, and indicators relevant to the assessment [49][50][51][52].…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we opted to use the multidimensional analysis method, which considers a range of criteria influencing the resilience of rural settlements. Most recent research commonly employs the Analytic Hierarchy Process (AHP) methodology for conducting multicriteria assessments across multiple research areas [46][47][48]. The AHP method provides a systematic framework for decision-making by establishing a hierarchical structure that captures the various dimensions, criteria, and indicators relevant to the assessment [49][50][51][52].…”
Section: Methodsmentioning
confidence: 99%
“…Selecting a landfill location that is remote from sensitive land uses and residential areas is important. Furthermore, the landfill has to be planned and run to reduce these adverse effects [26].…”
Section: A Land Fill Locationmentioning
confidence: 99%
“…AHP allows decision-makers to assess the significance of various factors. By assigning weights to these factors, decision-makers can select the best alternatives based on their maximum weighted values [20]. In 1981, Hwang and Yoon proposed the TOPSIS technique for calculating MCDM issues using multiple options.…”
Section: Introductionmentioning
confidence: 99%
“…The AHP-TOPSIS technique is a hybridized MCDM process used to determine the most suitable material among numerous alternatives. This has proven to be a reliable MCDM process that produces good and precise outcomes for complex problems [20,23]. Hambali et al [13] used the AHP technique and found that glass-fiberreinforced composites were the most appropriate materials for fabricating automobile bumpers.…”
Section: Introductionmentioning
confidence: 99%